Short term outcomes after robot assisted and open cystectomy - A nation-wide population-based study. Issue 4 (April 2023) - Bergengren, Oskar; Belozerov, Alexej; Bill-Axelson, Anna; Garmo, Hans; Hagberg, Oskar; Aljabery, Firas; Gårdmark, Truls; Jahnson, Staffan; Jerlström, Tomas; Malmström, Per-Uno; Sherif, Amir; Ströck, Viveka; et al.
Abstract: Introduction: We aimed to compare short term outcomes after robot assisted radical cystectomy (RARC) and open radical cystectomy (ORC) for urinary bladder cancer in a large population. Materials and methods: We included all patients without distant metastases who underwent either RARC or ORC with ileal conduit between 2011 and 2019 registered in the Bladder cancer data Base Sweden (BladderBaSe) 2.0. Primary outcome was unplanned readmissions within 90 days, and secondary outcomes within 90 days of surgery were reoperations, Clavien 3–5 complications, total days alive and out of hospital, and mortality. The analysis was carried out using multivariate regression models. Results: Out of 2905 patients, 832 were operated with RARC and 2073 with ORC. Robotic procedures were to a larger extent performed during later years, at high volume centers (47% vs 17%), more often for organ-confined disease (82% vs. 72%) and more frequently in patients with high socioeconomic status (26% vs. 21%). Patients operated with RARC were more commonly readmitted (29% vs. 25%). In multivariable analysis RARC was associated with decreased risk of Clavien 3–5 complications (OR 0.58, 95% CI 0.47–0.72), reoperations (OR 0.53, 95% CI 0.39–0.71) and had more days alive and out of hospital (mean difference 3.7 days, 95% CI 2.4–5.0). Conclusion: This study illustrates the "real-world" effects of a gradual and nation-wide introduction of RARC. Patients operated with RARC had fewer major complications and reoperations but were more frequently readmitted compared to ORC. The observed differences were largely due to more wound related complications among patients treated with ORC.